Making Sense of Student–Teacher Relationships: Teacher Educator and Candidate Engagement with the Relational Practices of Teaching. (3rd April 2018) - Phillippo, Kate; Brown, Elizabeth Levine; Blosser, Allison
ABSTRACT: Although research on student–teacher relationships (STRs) consistently demonstrates STRs' association with student achievement and well-being, teachers typically receive limited guidance regarding how to cultivate these relationships. Efforts to promote teacher dispositions toward STRs and learning of relational practices—practices that ground strong STRs—are promising but scattered. This case study, which analyzes observation and interview data, program materials, and teacher candidate artifacts, extends knowledge in this area. The authors explore how one purposefully selected program, unique in its efforts to promote relational practices, incorporated relevant programmatic and instructional structures, and how candidates in turn developed relational practices. Faculty stressed STRs' importance but hesitated to didactically teach relational practices. This stance encouraged instructors' relational practice teaching and generated promising ideas about relational practice teaching. It also led to varied, idiosyncratic relational practice repertoires among candidates. These findings inform discussion of how and whether teacher educators might further incorporate relational practice teaching and learning.